2004
DOI: 10.1124/jpet.103.063214
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effects of PJ34 [N-(6-Oxo-5,6-dihydrophenanthridin-2-yl)-N,N-dimethylacetamide.HCl], a Selective Inhibitor of Poly(ADP-Ribose) Polymerase, in Experimental Allergic Encephalomyelitis Are Associated with Immunomodulation

Abstract: Poly(ADP-ribose) polymerase (PARP) activity has been implicated in the pathogenesis of several central nervous system (CNS) disorders. For example, the presence of extensive poly-(ADP)ribosylation in CNS tissues from animals with experimental allergic encephalomyelitis (EAE) indicates that PARP activity may be involved in this inflammatory disease process. Using PJ34 [N-(6-oxo-5,6-dihydrophenanthridin-2-yl)-N, N-dimethylacetamide.HCl], a selective PARP inhibitor, we studied the mechanisms through which PARP ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 38 publications
(52 reference statements)
4
56
0
4
Order By: Relevance
“…Multiple PARPs inhibitors [3AB (Durkacz et al, 1980), PJ-34 (Scott et al, 2004) and AG14361 (Veuger et al, 2003)] were tested and gave similar results (data not shown). In addition, HeLa cells exposed to H 2 O 2 (1 mM) had delayed G3BP-mediated SG formation upon PARP inhibition with ABT-888 (supplementary material Fig.…”
Section: Journal Of Cell Sciencementioning
confidence: 58%
“…Multiple PARPs inhibitors [3AB (Durkacz et al, 1980), PJ-34 (Scott et al, 2004) and AG14361 (Veuger et al, 2003)] were tested and gave similar results (data not shown). In addition, HeLa cells exposed to H 2 O 2 (1 mM) had delayed G3BP-mediated SG formation upon PARP inhibition with ABT-888 (supplementary material Fig.…”
Section: Journal Of Cell Sciencementioning
confidence: 58%
“…20,[23][24][25][26] PJ34 is one of the most potent inhibitors of PARP-1 developed, 36 and prior studies show that it readily crosses the blood-brain barrier. [37][38][39] Although characterized as a PARP-1 inhibitor, it is likely that this agent also acts on other PARP family members. PJ34 does not have any known effects at other sites, but such effects cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the enzyme positively regulates activation of macrophages (8,9,35), microglia (7,36), granulocytes (37), lymphocytes (6,13,14), as well as TNF-␣-challenged endothelial cells (38). Also, parp-1 null mice are resistant to endotoxic shock (39), and PARP-1 inhibitors provide protection in models of pleuritis (40), arthritis (41), asthma (42), colitis (43,44), allergic encephalomyelitis (6,15,45), and other autoimmune disorders (46). In this context, the present findings point to the negative regulation of DCs by PARP-1 inhibitors as a key mechanism through which this class of drugs suppresses the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, numerous reports demonstrate that PARP-1 and PAR formation positively regulate transcription in several types of immune cells (4 -7), as well as macrophage activation (8,9), granulocyte migration (10,11), and T cell proliferation (6,12,13). Also, PARP-1 inhibition increases Ab class-switching (14), and alters Ab production during the autoimmune response in the CNS (15). Additional reports underscore the active role of poly ADP-ribosylation in immune activation of microglia and astrocytes (5,7,16).…”
mentioning
confidence: 99%